2018
DOI: 10.1039/c8ay01389f
|View full text |Cite
|
Sign up to set email alerts
|

Forensics in hand: new trends in forensic devices (2013–2017)

Abstract: Forensic chemistry is the application of analytical chemistry to forensic analysis and is today one of the hot topics in the scientific literature and this review discusses works published between 2013 and 2017 regarding portable or potentially portable analytical methods that can be used in different areas of forensic chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 365 publications
0
17
0
3
Order By: Relevance
“…Moreover, in recent years there has been an observable effort by researchers and stakeholders within the industry to develop new technologies and processes aimed at anti-counterfeiting and authenticity checking, supported by initiatives like the pan-European food integrity project [56]. Key to this effort is the development of sensors and rapid methods for the analysis of suspect products, particularly those that are field-portable and can be used at point-of-sale or distribution [44,53,57].…”
Section: Adulteration Fraud and Public Safetymentioning
confidence: 99%
“…Moreover, in recent years there has been an observable effort by researchers and stakeholders within the industry to develop new technologies and processes aimed at anti-counterfeiting and authenticity checking, supported by initiatives like the pan-European food integrity project [56]. Key to this effort is the development of sensors and rapid methods for the analysis of suspect products, particularly those that are field-portable and can be used at point-of-sale or distribution [44,53,57].…”
Section: Adulteration Fraud and Public Safetymentioning
confidence: 99%
“…Human expert panels are not suitable for the analysis of such samples, especially in cases when pathological conditions or metabolic disorders are investigated. These fluids are mainly composed of water and a small amount of biomarkers such as proteins, amino acids, and various organic and inorganic compounds [52]. The MSS discussed in this review are promising tools for the monitoring of such biomarkers, since they work in complex liquid media.…”
Section: Medical Analysismentioning
confidence: 99%
“…2,3 Thus, they provide an alternative method for clinical, environmental, forensics, and food quality control analysis. [4][5][6] Initially, colorimetric detection was the main technique coupled to PADs due to their simplicity. In 2009, Dungchai et al 7 reported the rst PAD based on electrochemical detection (ePAD).…”
Section: Introductionmentioning
confidence: 99%